Transformasi Data Statistik Menjadi Visual Interaktif Menggunakan Streamlit: Studi Kasus BPS Kota Mojokerto - Oktaviarini, kamilia nabila; Wahyuni, Eka Dyar; Sari, Reisa Permata (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
This study aims to transform the presentation of statistical data at the Central Bureau of Statistics (BPS) of Mojokerto City to be more interactive and accessible to the public. The previous data presentation through the graph menu on the Dakocantik mobile application relied on Excel-based visualizations, which were deemed less effective. To address this issue, this research developed a web-based dashboard using Streamlit, providing interactive and informative data visualization. The research methods included literature studies, interviews, data visualization, and system integration. The development process encompassed data source identification, extraction, cleaning, mapping, and storage before visualization using Streamlit. The dashboard was integrated with the Dakocantik mobile application via the web view feature, enabling users to access interactive statistical data directly from their mobile devices. The study's findings indicate that the developed dashboard successfully enhanced data accessibility and understanding among the public. Feedback from 13 respondents revealed that 92.3% found the dashboard easy to understand, and 84.6% assessed its features and interface as user-friendly for accessing data. Suggestions from users included improving loading times and enabling automatic data updates to enhance user experience further